Clinical outcomes of pediatric extracorporeal life support: Single center experience : Clinical outcomes of pediatric extracorporeal life support - Yazıcı Özkaya, Pınar; Metin, Hamdi; Zararcı, Kazım; Ersayoğlu, İrem; Turan, Gülizar; Tuncer, Osman Nuri; Karapınar, Bülent (Journal of Surgery and Medicine, 2022)
Background/Aim: The use of extracorporeal life support (ECLS) in children has notably increased over the last two decades, the indications for its use are expanding. According to the Extracorporeal Life Support Organization (ELSO) 2016 report, the rate of pediatric extracorporeal membrane oxygenation (ECMO) runs was 24% among all ECMO patients. A relationship between higher ECMO volume and mortality for neonates and adult patients supported with ECLS was reported. Different mortality rates were reported for different diagnostic and age groups for ECMO patients. The objective of this study was to describe our experience with pediatric ECMO. Methods: A retrospective cohort study was conducted on patients between 1 month and 18 years who underwent ECMO treatment in a pediatric intensive care unit from January 2015 to June 2022. Patients’ characteristics, outcomes, and complications were recorded. Results: A total of 22 children underwent ECMO during the study period. The median age of the patients was 4.5 years (ranging from 2 months to 18 years). Eight (36.4%) patients required venoarterial (VA) ECMO, and 14 patients (63.6%) required venovenous (VV) ECMO. Among the eight children who underwent VA ECMO, central cannulation was performed in 62.5% of cases. Seven children who required VV ECMO were cannulated with a double lumen catheter (42.8%). Thirteen (59.1%) patients were successfully weaned from ECMO. Weaning rates were 25% and 78.5% for VA and VV ECMO, respectively. Among 22 patients, overall hospital mortality was 72.7%. Mortality rates were 87.5% and 64.2% for VA and VV ECMO. Five patients (22.7%) survived to hospital discharge. Conclusion: Extracorporeal life support is one of the life-saving treatment modalities. This study found that the children requiring VA ECMO had a higher mortality rate than children requiring VV ECMO, a result that is consistent with the ELSO registry report. In our study, children requiring VV ECMO had a higher weaning rate than the ELSO registry data. However, they had a lower survival to discharge rate than the ELSO registry data. We feel that by describing this case series, the spread of ECMO practice may be supported in Turkey.